Living system design Studio: From digital to fabrication process - Paio, A. (2022)
Various approaches have been developed to deal with digital tools in architecture design process. The most recent is responsive architecture. This paper presents the results of a design studio based in an interdisciplinary collaboration research at Vitruvius Fablab-ISCTE IUL. The main goal was to explore the new digital technologies to generate a Discursive Wall – Living System that physically responds to movement, interacting spatially and temporally with the environment and its inhabitants.